2007
DOI: 10.1002/dc.20616
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell carcinoma and chronic lymphocytic leukemia (collision tumor) of the arm: A diagnosis by fine‐needle aspiration biopsy

Abstract: Simultaneous involvement of the same anatomical site by two different primary malignant tumors is rare. Cases of hematopoietic malignancies associated with breast and skin neoplasms have been described. The association of chronic lymphocytic leukemia (CLL) and Merkel cell carcinoma (MCC) has been established, although the cause for this association is still unclear. There are reports of MCC metastatic to lymph nodes involved by CLL. We report the case of a 57-year-old man with history of CLL with concurrent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…The negativity of specific markers for these malignancies has confirmed the MCC diagnoses. Among the neuroendocrine markers, NSE and CD56 had the highest frequency of positivity when performed (100 % positive), followed by CK20 (95 %); synaptophysin showed a twice higher ''sensitivity than chromogranin, when both were performed (73 vs 36 %); CK MNF116 showed a paranuclear dot-like pattern in most cases as also found in other series [16][17][18][19]. Domagala et al [35] demonstrated that these Bbuttons^staining for cytokeratin showed a paranuclear location and represent the equivalent of the intermediate filaments seen by electron microscopy.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The negativity of specific markers for these malignancies has confirmed the MCC diagnoses. Among the neuroendocrine markers, NSE and CD56 had the highest frequency of positivity when performed (100 % positive), followed by CK20 (95 %); synaptophysin showed a twice higher ''sensitivity than chromogranin, when both were performed (73 vs 36 %); CK MNF116 showed a paranuclear dot-like pattern in most cases as also found in other series [16][17][18][19]. Domagala et al [35] demonstrated that these Bbuttons^staining for cytokeratin showed a paranuclear location and represent the equivalent of the intermediate filaments seen by electron microscopy.…”
Section: Discussionsupporting
confidence: 50%
“…The definitive diagnosis of MCC is usually established only after surgical biopsy, but an increasing role for FNC has been demonstrated in literature [16][17][18][19]. With the exception of a very large series [18], very few papers dealing with the cytopathology of MCC on FNC samples have been published so far and mostly are case reports [16,17,[20][21][22], with no great details in the possible patterns and cytological description.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…described, [19][20][21][22][23] but, to our knowledge, this is the first quantitation of the degree to which MCC is overrepresented in this disease. We acknowledge the potential for referral bias in our series because patients who are immune suppressed may be more likely to be seen in tertiary medical centers.…”
Section: Discussionmentioning
confidence: 84%